Sonographic assessment of thickness of normal diaphragm by B mode ultrasound - Devkota, Karun; Gupta, Mukesh Kumar (Journal of Kathmandu Medical College, 2022)
Background: The thickness of diaphragm and diaphragmatic thickness fraction can be assessed by ultrasonography which can be used in early detection of the neuromuscular conditions and follow-up. Objectives: To measure the thickness of diaphragm during inspiration and expiration; and diaphragmatic thickness fraction by B mode ultrasound in healthy patients. Methods: An analytical cross-sectional study was conducted in 260 patients. Data were collected from 2020 July 10 to 2021 July 9 in Department of Radiology, BPKIHS after ethical clearance. Patients who were referred for sonographic evaluation and without neurological complains were included. Purposive sampling was done. Inferential statistical analysis was done applying SPSS v.11.5. Results: Mean diaphragmatic thickness on deep inspiration was found to be 2.80 ± 0.57 mm (95% CI 2.73-2.87 mm) and 2.71 ± 0.53 mm (95% CI 2.64-2.77 mm) on right and left side respectively. Mean diaphragmatic thickness on end expiration was found to be 2.01 ± 0.41 mm (95% CI 1.96-2.06 mm) and 1.97 ± 0.40 mm (95% CI 1.92-2.01 mm) respectively on right and left side. Mean diaphragmatic thickness fraction was observed 40 ± 7.79% (22-67%) and 38 ± 7.98% (22- 60%) on right and left side respectively. The mean difference between right and left side on inspiration was found to be statistically significant. A weak positive correlation of diaphragmatic thickness with BMI on both sides and on both during inspiration and expiration was seen. There was no statistically significant correlation of diaphragmatic thickness fraction with age and BMI. Conclusion: Sonographic diaphragm thickness measurement and diaphragm thickness fraction can provide both anatomical and physiological evaluation quickly.